STUDI INTERAKSI OBAT PADA PENGOBATAN PASIEN DIABETES MELLITUS YANG DISERTAI TROMBOSIS DI RSUP. Dr. WAHIDIN SUDIROHUSODO MAKASSAR - Rachmat Kosman (As-Syifaa Jurnal Farmasi, 2011)
The aim of this study was to determine the interactions of drugs that used to treat the Diabetes Mellitus patiens espoused by Trombosis at RSUP. DR. Wahidin Sudirohusodo in Makassar. The research concerning by means non-experimental with descriptive approach was to collect the data with retrospectively compared take from medical data then to seach the drugs that interacting each other on Diabetes Mellitus patient espoused by Trombosis at RSUP. DR. Wahidin Sudirohusodo in Makassar. From determinable research result that in the year 2007 interaction  among drug of Diabetes Mellitus ( Sulfonylurea) with the drug antitrombosis ( Aspirin) that is equal to 61,6% while in the year 2008 equal to 38,4%, with the interaction type that is interaction pharmacokinetics in the form of distribution interaction, and effect generated by that is effect Pharmacodynamik.Key Words : Interaction, Diabetes mellitus, Thrombosis